2014
DOI: 10.1124/jpet.113.211334
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxytryptamine–Mediated Neurotransmission Modulates Spontaneous and Vagal-Evoked Glutamate Release in the Nucleus of the Solitary Tract Effect of Uptake Blockade

Abstract: The effect of blockade of either 5-hydroxytryptamine (5-HT)/ serotonin transporter (SERT) with citalopram or the organic cation transporter 3 (OCT3)/plasma membrane monoamine transporter (PMAT) with decynium-22 (D-22) on spontaneous and evoked release of 5-HT in the nucleus tractus solitarius (NTS) was investigated in rat brainstem slices treated with gabazine. 5-HT release was measured indirectly by changes in the frequency and amplitude of glutamatergic miniature excitatory postsynaptic currents (mEPSCs) [in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 36 publications
2
17
1
1
Order By: Relevance
“…The B3 region, and in particular the raphe magnus, receives massive projections from the dlPAG (Fardin et al, 1984) that, in turn, provides a significant set of serotonergic projection to the NTS (Schaffar et al, 1988;Thor and Helke, 1987). Thus dlPAG activation may be at the origin of serotonin release into the NTS, to ultimately activate presynaptic 5-HT 3a receptors (Hosford et al, 2014), as found previously (Bernard et al, 2008). The…”
supporting
confidence: 51%
“…The B3 region, and in particular the raphe magnus, receives massive projections from the dlPAG (Fardin et al, 1984) that, in turn, provides a significant set of serotonergic projection to the NTS (Schaffar et al, 1988;Thor and Helke, 1987). Thus dlPAG activation may be at the origin of serotonin release into the NTS, to ultimately activate presynaptic 5-HT 3a receptors (Hosford et al, 2014), as found previously (Bernard et al, 2008). The…”
supporting
confidence: 51%
“…While corticosterone inhibits human OCT3 with greater potency than OCT1 and OCT2, it is much less potent for PMAT than for OCT1‐3 ( Table ) . Due to the lack of a PMAT‐specific inhibitor, sensitivity to D22 but not to corticosterone has been used as an indirect approach in many cell and tissue studies to discern PMAT activity from those of the OCTs . Recently, we identified the fluorescent MPP + analog, IDT307, as a transportable substrate for PMAT and developed a fluorescence assay for rapid identification and characterization of PMAT inhibitors .…”
Section: Molecular and Functional Characteristics Of Pmatmentioning
confidence: 99%
“…Interestingly, in the present experiments in vivo and those in the slice (Hosford et al . ), these data indicate that SERT does function in the NTS, but is not involved in vagally evoked release of 5‐HT. This implies that PMAT must be located much nearer to the site of this evoked 5‐HT release than SERT.…”
Section: Discussionmentioning
confidence: 65%
“…; Wan & Browning, ; Hosford et al . ). The source of this 5‐HT release has not been determined; it may be from vagal afferent terminals and/or 5‐HT terminals within the NTS originating from other brain areas.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation